The Road to Professionalism in Medical Informatics: A Proposal for Debate - Heathfield, H. A.; Wyatt, J. (Methods of Information in Medicine, 1995)
Medical Informatics has not as yet reached professional status. However, as an expanding and increasingly important discipline in the delivery of healthcare, it is important that it strives towards professionalisation. In this article we consider the nature of professionalism, its potential benefits and associated costs. We examine the potential for Medical Informatics to become a professional discipline and how far it has succeeded in this to date, describing three possible scenarios for the future of the discipline. We suggest steps towards the professionalisation of Medical Informatics and the roles of key players, including academia, system developers, purchasers and users, and professional societies. We also put forward some possible criteria for a Medical Informatics Professional. Finally, we make some general observations concerning the way forward.
Keywords: Medical Informatics; Professionalism; Education; System Development